A Systematic Review of Parental Involvement in the Education of Their Children - Romsaitong, Pandate; Sricha Brown, Sumien (ASEAN Journal of Education, 2023)
This systematic review takes a comprehensive look at the literature surrounding the issue of parent involvement in the education of their children. The study provides an in-depth examination into scholars and their theoretically grounded study to explore the correlation between parent involvement in their children’s education and the academic success of children. This systematic review finds that, while this is a complicated topic and the nature of parental involvement in education can vary, there is a well-supported consensus among social scientists that there is a positive impact on a child’s development when parents are involved in their child’s education in some capacity. Parent-teacher relationships have proven to enhance education as well. By fostering, developing, and maintaining a strong relationship between parents and teachers, parents will be confident in their ability to support their child’s education. Heterogenous parents vary in their conceptual understanding of education thus impacting their beliefs on engagement. Despite such benefits of parental involvement, barriers inclusive of under-educated parents and broken school systems adversely affect the quality of their child’s education. Race and ethnicity hamper African American and Latino parents as well as parents from Kenya and ASEAN from fully engaging in their child’s education. This review demonstrates how the relationship between parents, children, and educators can be better organized to maximize this positive effect. The study ends with suggestions as to how these findings can be implemented towards a better education experience.